Humour discourse in ESL classrooms: a critical literature review - Sorayyaei Azar, Ali; Ying, Huang (European journal of humour research, 2025)
This critical literature review explores the functions, pedagogical applications, and implications of humour discourse in English as a Second Language (ESL) classrooms, drawing on ten empirical studies published between 2021 and 2025. Guided by three research questions and the Scopus database, the review investigates the types of humour employed, the strategies used by educators, and the broader theoretical and practical implications for English language teaching. The findings reveal that humour functions as a multi-modal and context-sensitive discourse resource that supports not only language comprehension and vocabulary retention but also classroom rapport, affective safety, and cultural literacy. Applications range from verbal jokes and puns to digital memes, audiovisual satire, and identity-affirming classroom practices. However, the review also identifies critical tensions—particularly regarding the ethical boundaries of humour, its potential for exclusion, and its unequal effects across different learner identities and contexts. While humour is often praised for its motivational benefits, its long-term impact on linguistic development remains under-explored. The study calls for a shift from viewing humour as incidental to recognising it as a complex, socially situated pedagogical tool. It also advocates for the inclusion of humour pedagogy in teacher training programmes and recommends future research that addresses cognitive outcomes, student-generated humour, and the integration of humour in digital learning environments.